Plasmid-based controls to detect rpoB mutations in Mycobacterium tuberculosis by quantitative polymerase chain reaction-high-resolution melting - Silva, Joas Lucas da; Leite, Gabriela Guimaraes Sousa; Bastos, Gisele Medeiros; Lucas, Beatriz Cacciacarro; Shinohara, Daniel Keniti; Takinami, Joice Sayuri; Miyata, Marcelo; Fajardo, Cristina Moreno; Luchessi, André Ducati; Leite, Clarice Queico Fujimura [UNESP]; Cardoso, Rosilene Fressatti; Hirata, Rosario Dominguez Crespo; et al. (Instituto Oswaldo Cruz, Ministério da Saúde, 2013)
Quantitative polymerase chain reaction-high-resolution melting (qPCR-HRM) analysis was used to screen for mutations related to drug resistance in Mycobacterium tuberculosis. We detected the C526T and C531T mutations in the rifampicin resistance-determining region (RRDR) of the rpoB gene with qPCR-HRM using plasmid-based controls. A segment of the RRDR region from M. tuberculosis H37Rv and from strains carrying C531T or C526T mutations in the rpoB were cloned into pGEM-T vector and these vectors were used as controls in the qPCR-HRM analysis of 54 M. tuberculosis strains. The results were confirmed by DNA sequencing and showed that recombinant plasmids can replace genomic DNA as controls in the qPCR-HRM assay. Plasmids can be handled outside of biosafety level 3 facilities, reducing the risk of contamination and the cost of the assay. Plasmids have a high stability, are normally maintained in Escherichia coli and can be extracted in large amounts.
Keywords: drug resistance; rifampicin; Mycobacterium tuberculosis